Sosialisasi Penyusunan Laporan Keuangan di Desa Wisata Sayan, Kabupaten Gianyar - Anak Agung Gede Oka Geria (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The Study Program of Hospitality Accounting Management has the duty and responsibility to carry out the Tri Dharma of Higher Education, one of which is Community Service. This time we held Community Service in Sayan tourism village, in the form of socialization of Financial Reports. Generally, it can be concluded that the community service of the Study Program was in accordance with the needs and expectations of the community in the village, they hope there would be other activities such as training and mentoring in composing financial report. Keywords: socialization, financial reports, accounting hospitality,